#### Answer

6

#### Work Step by Step

See Factorial Notation, page 696:
$n!=n(n-1)(n-2)\cdots(3)(2)(1)$
and, by definition, $0!=1$
------------
$(\displaystyle \frac{12}{4})!=(3)!=3\times 2\times 1=6$

Published by
Pearson

ISBN 10:
0321867327

ISBN 13:
978-0-32186-732-2

6

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.